Cold-water extracts of Grifola frondosa and its purified active fraction inhibit hepatocellular carcinoma in vitro and in vivo. Issue 13 (July 2016) - Lin, Chia-Hung; Chang, Ching-Yao; Lee, Kuan-Rong; Lin, Hui-Ju; Lin, Wu-Chou; Chen, Ter-Hsin; Wan, Lei
Mushrooms are used in traditional Chinese medicine to treat a variety of diseases. Grifola frondosa (GF) is an edible mushroom indigenous to many Asian countries with a large fruiting body characterized by overlapping caps. In particular, GF is known for its anti-tumor activity, which has been targeted by scientific and clinical research. This study aimed to investigate the effects of the cold-water extract of GF (GFW) and its active fraction (GFW-GF) on autophagy and apoptosis, and the underlying mechanisms in vitro and in vivo . Our results revealed that GFW and GFW-GF inhibited phosphatidylinositol 3-kinase (PI3K) and stimulated c-Jun N-terminal kinase (JNK) pathways, thereby inducing autophagy. We also demonstrated that GFW and GFW-GF inhibited proliferation, induced cell cycle arrest, and apoptosis in Hep3B hepatoma cells. GFW and GFW-GF markedly arrested cells in S phase and promoted cleavage of caspase-3 and -9. In addition, GFW and GFW-GF decreased the expression levels of the anti-apoptotic proteins protein kinase B and extracellular signal-regulated kinase. We also found that GFW significantly inhibited tumor growth in nude mice implanted with Hep3B cells. Our work demonstrates that GF and its active fraction inhibit hepatoma growth by inducing autophagy and apoptosis.